1.664 / 5.000 Notary's Liability for Signature Forgery by Applicant (Civil Case Study Number 256/PDT/2020/PT.BDG) - Kurniasih, Kristin (Jurnal Konstatering, 2024)
The legal system applicable in Indonesia regarding and determining the existence of written evidence is in accordance with the provisions in Article 1866 of the Civil Code, hereinafter referred to as the Civil Code, which states that the means of evidence include written evidence, witness evidence, suspicion, confession and oath. The method used in this study is the normative legal research method. The approach method used is a qualitative approach. The types and sources of data use primary and secondary data. The data analysis method used in this study is prescriptive. The results of this study are: Notary's Liability for the Deed of Transfer of Rights and Power of Attorney made before Notary DF, S.H, M.Kn. Number 6 and 7 dated November 30, 2009 in Cibinong, Bogor Regency, which contain elements of forged signatures (in the figure), the Notary cannot be held responsible, either civilly or criminally. As a result of the unlawful act in the form of forgery of the signature of the person appearing in the Deed of Transfer of Rights and Power of Attorney made before Notary DF, S.H, M.Kn. Number 6 and 7 dated November 30, 2009 in Cibinong, Bogor Regency, the notarial deed is null and void. On the grounds that the element of a "lawful cause" is not met, which is one of the objective requirements for the validity of an agreement.